2022
DOI: 10.1055/s-0042-1756701
|View full text |Cite
|
Sign up to set email alerts
|

Is Vitamin D Deficiency Prothrombotic? A Systematic Review

Abstract: Observational studies indicate a relationship between vitamin D deficiency and an increased risk of venous and arterial thrombotic events, but the underlying mechanisms behind this association are uncertain. This systematic review explores if there is an association between decreased vitamin D levels and a prothrombotic profile. The systematic literature search initially identified 3,214 studies (published until December 21, 2021) investigating the relationship between vitamin D and numerous hemostatic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(318 reference statements)
0
2
0
Order By: Relevance
“…15,51,67,72 No significant differences were shown between the 2 groups of pregnant women in the present study when comparing the additional hemostatic parameters. According to our recent systematic review, 73 findings on the effect of vitamin D on hemostatic parameters in nonpregnant populations have generally been inconclusive. However, of particular note, Blondon et al 15 suggested that the influence of vitamin D status on hemostasis may be restricted to individuals with a severe vitamin D deficiency (<25 nmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…15,51,67,72 No significant differences were shown between the 2 groups of pregnant women in the present study when comparing the additional hemostatic parameters. According to our recent systematic review, 73 findings on the effect of vitamin D on hemostatic parameters in nonpregnant populations have generally been inconclusive. However, of particular note, Blondon et al 15 suggested that the influence of vitamin D status on hemostasis may be restricted to individuals with a severe vitamin D deficiency (<25 nmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…We continue the discussion of prothrombotic pathways with the next contribution, from the authorship team of Rüdiger and colleagues, who address the question of whether Vitamin D deficiency is prothrombotic. 11 Observational studies indicate a relationship between vitamin D deficiency and an increased risk of venous and arterial thrombotic events, but the underlying mechanisms behind this association remain uncertain. The authors provide a systematic review to explore if there is an association between decreased vitamin D levels and a prothrombotic profile.…”
Section: Tablementioning
confidence: 99%